Olfactory Enrichment in California Sea Lions (Zalophus californianus): An Effective Tool for Captive Welfare?. Issue 1 (2nd January 2017) - Samuelson, Mystera M.; Lauderdale, Lisa K.; Pulis, Kelly; Solangi, Moby; Hoffland, Tim; Lyn, Heidi
Abstract : In the wild, California sea lions ( Zalophus californianus ) are exposed to a wide variety of sensory information, which cannot be replicated in captive environments. Therefore, unique procedures are necessary for maintaining physiological and psychological health in nonhuman animals in captivity. The effects of introducing natural scents to captive enclosures have been investigated in a variety of species, yet they have not been examined in marine mammals. This project explored the behavioral effect of scent added to the environment, with the goal of improving the welfare of sea lions in captivity. Two scent types were introduced: (a) natural scents, found in their native environment, and (b) non-natural scents, not found in their native environment. This study examined not only scent enrichment but also the possible evolutionary underpinnings of pinniped olfaction. Scent enrichment was found to significantly impact sea lion behavior as demonstrated by a reduction in pattern swimming, an increase in habitat utilization, and a reduction in stereotypical behavior. However, there were no differences in behavior between natural and non-natural scent conditions.